2014
DOI: 10.1007/s12078-014-9172-5
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Olfactory Behavior in Namibian and Czech Children

Abstract: Sex differences in olfaction are well established, but explanations for those sex differences remain incomplete. One contributing factor could be individual-or cultural-level differences in exposure to odors. We tested whether frequent engagement with common sources of domestic odors (cooking, domestic animals, siblings) was linked to individual differences in olfactory reactivity and awareness among children in southern Namibia, and also compared study populations in southern Namibia and the Czech Republic us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Children’s olfactory reactivity and awareness did not vary with respect to their age or verbal fluency, which were correlated, as could be expected 41 . In previous studies, children’s olfactory reactivity and awareness were found to increase with age 4 , 5 , 7 , which was ascribable to the children’s progressively better memory and verbal fluency. The absence of such links in the present study could be attributed to the low variability in age.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Children’s olfactory reactivity and awareness did not vary with respect to their age or verbal fluency, which were correlated, as could be expected 41 . In previous studies, children’s olfactory reactivity and awareness were found to increase with age 4 , 5 , 7 , which was ascribable to the children’s progressively better memory and verbal fluency. The absence of such links in the present study could be attributed to the low variability in age.…”
Section: Discussionmentioning
confidence: 81%
“…Children’s olfactory reactivity and awareness showed a gender difference in favour of girls, which is in line with the study by Saxton, et al . 4 . However, one of the key issues when interviewing children is that they can interpret the researcher’s questions as a search for the “right answer” and thus may say what they believe he or she wants to hear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations